Cryogenic strength-ductility mechanism of heterostructured CoCrFeMnNi high-entropy alloy - Chengchi Wang; Yu Cao; Jingge Li; Wenhai Peng; Dongqun Xin; Jie Chen (Journal of Materials Research and Technology)
A typical heterogeneous structure with ultrafine grains embedded in coarse grains is obtained by partial recrystallization annealing, which exhibits excellent cryogenic mechanical properties. Researches reveal that the hard domains, high-density GND pile-ups, and multi-axial stress states of heterogeneous structures provide nucleation positions and critical stresses for triggering twinning, meanwhile, nanotwins can refine the hard domain grains to improve the heterogeneity of heterogeneous structures during cryogenic plastic deformation. Therefore, the heterostructure-twinning interaction is identified as the key factor in realizing the excellent cryogenic strength-ductility synergy of the heterostructured CoCrFeMnNi high-entropy alloy. Besides, the nucleation and propagation of generous microcracks at single-order twin boundaries induced by the excellent twinning activity result in the rapid fracture of the heterostructured samples, whereas the microcracks can hardly be observed nearby high-order nanotwins, which indicates that generating more high-order nanotwins is a promising guiding scheme to prepare the heterostructured materials with superior cryogenic mechanical properties.